Studying Public Policy an international policy (Bristol Policy Press, 2004)
Studying Public Policy organizes an impressive number of contributions?nineteen in all?from diverse scholars all around the world to bring to life the realities of policy making. The contributors use international case studies to demonstrate the challenges of public policy implementation and measurements of its success. Linked throughout by substantive commentary from editor Michael Hill, a leading author in the field, the book is divided into five sections, each covering a different aspect of the policy-making process: stability and change, agenda setting, policy formulation, implementation and governance, and globalism. Altogether these sections provide readers with a host of tools for understanding policy making as it actually happens.
Includes index
Keywords: Public Policy